Penerapan Tax Review Atas Pajak Penghasilan Sebagai Strategi Tax Planning Pada PT Kharisma Barokah Muliatama - Ani Oktaviani; Yeti Apriliawati (Indonesian Accounting Literacy Journal, 2021)
Tax planning produced based on tax review will be more effective because it is in accordance with the conditions and constraints experienced by the company. PT Kharisma Barokah Muliatama is an UMKM which is engaged in land transportation services. This study aims to examine the tax obligations and financial reports for three years which will be used as a strategy for the next year's tax planning. The research method used is qualitative and uses study data analysis techniques. Based on the tax review that has been done, the company has carried out its tax obligations for calculations, deposits and reports in accordance with tax regulations. However, there are sales of assets that are not recorded, so there is tax that must be deposited and reported. To avoid any findings during the audit, the company must pay and report taxes on the sale of these assets.